A new species of kukri snake (Squamata: Colubridae: Oligodon Fitzinger, 1826) from Con Dao Islands, southern Vietnam - Nguyen, Sang Ngoc; Nguyen, Vu Dang Hoang; Le, Son Hong; Murphy, Robert W. (Zootaxa, 2016)
We describe a new kukri snake, Oligodon condaoensis sp. nov., from Con Dao Islands, southern Vietnam based on the morphological characters of four specimens. It differs from other congeners by a combination of the following characters: medium size in adults (total length up to 552 mm); 17–17–15 dorsal scale rows; deeply forked hemipenes without spines and papillae, extending to subcaudal 13 or 14; 11–13 maxillary teeth, the posterior three being enlarged; cloacal plate undivided; head scalation complete; nasal divided; presubocular absent; 168–176 ventrals; 33–37 subcaudals; overall dorsal coloration dark gray, faint body stripes present or absent; and ventral coloration cream to dark gray without rectangular blotches. We also provide a list of 43 species of amphibians and terrestrial reptiles recorded from Con Dao Islands.